UTILIZATION OF FERMENTED Azolla Microphylla FLOUR MIXTURE AS FRESHWATER BAWAL FISH (Colossoma Macropomum) FEED TO ACCELERATE FISH GROWTH PROCESS - Ni’mah, Khairatun; Istyadji, Maya; Sari, Mella Mutika (Transpublika Publisher, 2023)
Bawal fish is popular in many Asian cuisines and is often served grilled, fried, or steamed. It is known for being a good source of protein and essential nutrients, making it a healthy and nutritious option for seafood lovers. Meanwhile, fermented Azolla flour contains high levels of nutrients, such as protein, vitamins, and minerals, which can help improve fish growth. The nutrients in the fermented Azolla flour can be utilized by the fish to build body tissues and accelerate body mass growth. The aim of this study is to evaluate the impact of using fermented Azolla microphylla flour in artificial feed for the growth of bawal fish fry and the best percentage of fermented Azolla microphylla flour in the feed to enhance fish growth. The study used a completely randomized design (CRD) with 1 factor, 5 treatments, and 2 replications. The treatments in this study were PA (30% FTA), PB (40% FTA), PC (50% FTA), PD (100% PK), PE (0% FTA) in the feed. The test feed was given at 5% of the biomass weight, twice a day at 07.00 and 17.00 WIB. The bawal fish fry used had an average size of 5.19 ± 0.71 cm and an average weight of 2.57 ± 0.08 g, with a stocking density of 15 fish/m3. The results of the study showed that the administration of fermented Azolla powder increased the growth of bawal fish fry. The use of 40% fermented Azolla microphylla flour (PB) produced the best results in terms of fish length growth at 4.85%, weight growth at 6.5%, and the highest protein content at 72.56% with the use of 30% Azolla microphylla fermentation.